2015
DOI: 10.2135/cropsci2014.10.0721
|View full text |Cite
|
Sign up to set email alerts
|

Two Decades of Molecular Marker‐Assisted Breeding for Resistance to Soybean Sudden Death Syndrome

Abstract: Novel tools to improve resistance to sudden death syndrome (SDS) and the underlying Fusarium root rot (FRR) caused by Fusarium virguliforme (Aoki) have been developed for soybean [Glycine max (L.) Merr.]. Eighteen resistance loci have been identified and confirmed over the past two decades (named Rfs1 to Rfs18). To select the beneficial alleles of 8 to 10 loci per cross needed for optimal resistance is a difficult task for plant breeders. Resistance mechanisms to FRR provide only partial protection. Crops cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 133 publications
(293 reference statements)
1
21
0
Order By: Relevance
“…Soybean sudden death syndrome (SDS), which is caused by a soilborne fungus F. virguliforme , is responsible for annual losses around US$190 million [ 18 ]. Breeding for SDS resistance is difficult because the interaction between F. virguliforme and soybean is quantitative [ 19 ]. Instead, it has been suggested that transgenic approaches may be suitable to manage SDS, and transgenic soybeans expressing exogenous toxin-specific antibody has been shown to reduce SDS foliar symptoms [ 18 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Soybean sudden death syndrome (SDS), which is caused by a soilborne fungus F. virguliforme , is responsible for annual losses around US$190 million [ 18 ]. Breeding for SDS resistance is difficult because the interaction between F. virguliforme and soybean is quantitative [ 19 ]. Instead, it has been suggested that transgenic approaches may be suitable to manage SDS, and transgenic soybeans expressing exogenous toxin-specific antibody has been shown to reduce SDS foliar symptoms [ 18 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…These include dip inoculation of sprouted seed in F. virguliforme spore suspension and planting in greenhouse mix [80,81,85], temperature-controlled water bath method [38], exposing cut stem to cell free culture filtrate [42], molecular marker-assisted breeding for resistance [60], toothpick inoculation and soil infestation methods [111], planting seeds in a mixture of 1 part inoculum with 20 part soil [64], using cones filled with steam-treated soil mix (2:1 sand: soil) and topped with 3 g of fungus infested white sorghum grains [25]. Navi and Yang (unpublished), modified greenhouse screening technique [80,81,85] to identify resistance sources in germplasm and explore efficacy tests of seed treatments with biocontrol agents (BCA) and or chemicals against SDS (Fig.…”
Section: Resistance Screening In Greenhouse Conditionsmentioning
confidence: 99%
“…Losses to SCN have been reduced by almost half since 1990, but it still remains a major problem in soybean (Lightfoot, 2015). SCN causes plant and root stunting and leaf chlorosis.…”
Section: Introductionmentioning
confidence: 99%
“…Sudden death syndrome (SDS) has been shown to be a facultative hemibiotrophic fungus (Li, 2009;Roy, 1997) that causes yield loss in soybean. The amount of loss has doubled every decade in the US, since 1990 (Wrather, 2001;Lightfoot, 2015). SDS, as a syndrome, is disease complex of both a root rot and a leaf scorch.…”
Section: Introductionmentioning
confidence: 99%